The selection of species of conservation concern under the USDA Forest Service's new planning requirements for wildlife - Grimes, Summer Star, author; Schultz, Courtney, advisor; Noon, Barry, committee member; Cheng, Tony, committee member (Colorado State University. Libraries, 2016)
In 2012, the USDA Forest Service finalized a planning rule that represents the most significant change in federal forest policy in nearly 30 years. All 155 national forests (and 20 national grasslands) must eventually update their management plans in accordance with the new regulations, which have significant implications for wildlife conservation planning. The agency selected eight “early adopter” forests as the first to implement the new planning rule. Given the contentious history of wildlife planning on national forests, there is a high level of interest amongst many audiences in the implementation of the new rule’s language – specifically for a new category of species: “species of conservation concern” (SCCs). The new rule requires the agency to maintain the viability of SCCs on national forests; however, due to uncertainty regarding the new rule’s language, concern exists regarding the management of and planning for SCCs. This research investigated the process of policy implementation during the early stages of forest plan revision on three adjacent early adopter forests to provide insight into the factors that are likely to influence wildlife planning decisions for SCCs across all national forests. Approximately 20 qualitative, semi-structured interviews with agency staff and external environmental partners revealed that traditional challenges of policy implementation were a continued barrier to wildlife planning; however, interviews also revealed cautious optimism that the agency is experiencing a positive paradigm shift in how they address ecosystem management, enabling them to move beyond administrative borders and see forests as part of a broader ecosystem – potentially resulting in a more integrated approach to wildlife management and habitat conservation. This study provides valuable insight into early-stage procedural determinations for wildlife planning on national forests for at-risk species and can serve as a valuable source of ‘lessons learned’ for subsequent forest plan revisions.